Study on microstructure characteristics and hole expansion mechanism of Ti–Nb–V microalloyed 900 MPa hot-rolled ferrite-bainite high hole expansion steel - Zhengtuan Li; Lei Liu; Qihe Xue; Chunjing Wu; Fenghui Lu; Zhengzhi Zhao (Journal of Materials Research and Technology)
In this study, a 900 MPa grade hot-rolled ferrite/bainite high hole expansion steel was developed using thermomechanical controlled processing (TMCP) and medium-temperature coiling with a Ti–Nb–V multi-microalloy design. The effects of cooling rates and coiling temperatures on the microstructure, mechanical properties, and hole expansion behavior were systematically investigated. The steel, coiled at 600 °C and cooled at a controlled rate (10–25 °C/s), demonstrated an excellent balance of strength and ductility, achieving a tensile strength of 901 MPa and elongation of 23%. The microstructure consisted of approximately 62% ferrite and 38% bainite, characterized by a uniform and fine grain distribution. The high coiling temperature increased the content of Ti–Nb–V composite precipitates, while reduced cooling times promoted the formation of smaller precipitates primarily along dislocation lines and grain boundaries. A hole expansion ratio of 77% was achieved due to the optimized grain morphology and phase ratio, with refined grains and high-angle grain boundaries impeding crack propagation. Additionally, the increased presence of secondary precipitates strengthened the soft phase ferrite and enhanced the coordinated deformation between ferrite and bainite. These combined effects significantly improved the steel's resistance to crack propagation during hole expansion, making it a promising material for applications requiring high strength and formability.